2018
DOI: 10.3390/nano8030132
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride Decorated Ball-Flower like Co3O4 Hybrid Composite: Hydrothermal Synthesis and Ethanol Gas Sensing Application

Abstract: Recently, semiconducting metal oxide (SMO) gas sensors have attracted the attention of researchers for high conductivity, labile features by environment, low cost, easy preparation, etc. However, traditional SMOs have some defects such as higher operating temperature and lower response value, which greatly limit their application in the field of gas sensor. In this work, the carbon nitride decorated ball-flower like Co3O4 composite was successfully synthesized via a facile hydrothermal method, the composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Ye et al 11 obtained graphene nanoplate (GN)-polyaniline (PANI) composites through in situ polymerization, which exhibited good sensor response for 100 ppm NH 3 at RT (15 ppm, $1.5%). Gong et al 12 successfully synthesized a g-C 3 N 4 modied ball-ower like Co 3 O 4 composite (Co 3 O 4 /pCNH) by a simple hydrothermal method. It was found that the Co 3 O 4 /pCNH composites exhibited a very high response to ethanol gas at 210 C (500 ppm, $30.2%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al 11 obtained graphene nanoplate (GN)-polyaniline (PANI) composites through in situ polymerization, which exhibited good sensor response for 100 ppm NH 3 at RT (15 ppm, $1.5%). Gong et al 12 successfully synthesized a g-C 3 N 4 modied ball-ower like Co 3 O 4 composite (Co 3 O 4 /pCNH) by a simple hydrothermal method. It was found that the Co 3 O 4 /pCNH composites exhibited a very high response to ethanol gas at 210 C (500 ppm, $30.2%).…”
Section: Introductionmentioning
confidence: 99%
“…EG and g-C 3 N 4 are ideal atomic thickness 2D substrates for anchoring nanomaterials. 12,13 In our previous work, EG was used as a substrate to synthesize CeO 2 / graphene nanoower composites. The sensitivity of CeO 2 / graphene composites for 100 ppm NO x was 10.39% at RT.…”
Section: Introductionmentioning
confidence: 99%
“…Deionized water was used in this work. The nanosheets of 2D g-C 3 N 4 and hexagonal 2D α-Fe 2 O 3 were synthesized according to previously reported methods [33][34][35]. In a typical synthesis, the 2D α-Fe 2 O 3 @g-C 3 N 4 photocatalyst was prepared using an ultrasonic assisted self-assembly method.…”
Section: Synthesismentioning
confidence: 99%
“…Several previous studies focusing on g-C 3 N 4 decorated various metal oxide composites proved that g-C 3 N 4 plays a very important role in the composites. It not only enlarges the specific surface area and prevents agglomeration of metal oxide nanoparticles, but also forms a heterojunction with MOSs and provides new chemical and structural properties [25,26,27]. Cao et al reported that SnO 2 /g-C 3 N 4 nanocomposites show a favorable response to ethanol by a facile calcination method [28].…”
Section: Introductionmentioning
confidence: 99%